A Novel CP Horn Antenna with Switchable Polarization by Single Port Feeding - Yangzhen Huang; Junping Geng; Xianling Liang; Ronghong Jin; Xudong Bai (International Journal of Antennas and Propagation)
A novel CP horn antenna with switchable polarization by single port feeding is presented. The antenna is composed of a coaxial-waveguide converter and a balance-cavity, a horn, a square-to-circular waveguide transition, and a stepped-septum polarizer, which simplify the feeding and can work on the left-hand or right-hand circular polarizations by manual exchanging the mounting position of the coaxial-waveguide converter and the balance-cavity. The antenna achieves an impedance bandwidth (3.88~5.12 GHz) of 27.5% and a 3 dB-AR (Axial Ratio) bandwidth of 18.6%, with the 3 dB-AR beamwidth of about 149°, and the antenna gain is over 13.3 dB in the available band.